2017
DOI: 10.1242/jeb.150946
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention in peacocks during assessment of rival males

Abstract: Males in many species compete intensely for access to females. In order to minimize costly interactions, they can assess their rivals' competitive abilities by evaluating traits and behaviors. We know little about how males selectively direct their attention to make these assessments. Using Indian peafowl (Pavo cristatus) as a model system, we examined how males visually assess their competitors by continuously tracking the gaze of freely moving peacocks during the mating season. When assessing rivals, peacock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Males display their trains to rivals; they do not rattle their trains, but train displays have been shown to form part of male-male aggressive behaviours, thus informing males’ assessments of rivals [29]. In this respect, size would count, and larger would be better.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Males display their trains to rivals; they do not rattle their trains, but train displays have been shown to form part of male-male aggressive behaviours, thus informing males’ assessments of rivals [29]. In this respect, size would count, and larger would be better.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, Yorzinski et al[29]demonstrated that peacocks assess rivals using cues similar to the cues that females use to assess males. One study found that females spent more time gazing at the lower train, which is lined with eyespots and fishtails, and the body during courtship displays[21];meanwhile, another study found that males spent more time gazing at the lower train eyespots and fishtail feathers and the body and wings of rival males[29]. This strongly suggests that the traits used in courtship displays are also used to assess rivals [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, one or both sexes may also produce intra-sexual signals that deter potential rivals [11,12]. Inter-and intra-sexual signals can be identical [11,13] or different [14][15][16]. For example, the boatwhistle vocalizations of male Lusitanian toadfish, Halobatrachus didactylus, have dual functions, serving a role during male-female courtship and as a male-male territorial signal [11].…”
Section: Introductionmentioning
confidence: 99%
“…Such sensory integration and attentional switches across different sensory modalities have been studied in depth (Yorzinski et al, 2017). In contrast, less is known about how animals coordinate multiple streams of information within a single modality.…”
Section: Introductionmentioning
confidence: 99%